Conversations about Astrophysics and Cosmology - Burton, Howard (Ideas Roadshow Collections., 2020)
Conversations About Astrophysics & Cosmology is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring 5 leading physicists with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection:1. Roger Penrose, co-recipient of the 2020 Nobel Prize in Physics and Emeritus Rouse Ball Professor of Mathematics at the Mathematical Institute at the University of.